H.G. Wells and all things Russian - Diment, Galya (Anthem Press, an imprint of Wimbledon Publishing, 2019)
'H. G. Wells and All Things Russian' examines Wells's keen interest in Russian culture and development, and how Russia and the Soviet Union were, in turn, profoundly influenced by his works and his visits to the country
Work consists of both items originally published in English and other items newly translated to English from the original Russian.
Keywords: Wells, H. G. -- (Herbert George), -- 1866-1946 -- Knowledge -- Soviet Union.; Wells, H. G. -- (Herbert George), -- 1866-1946 -- Criticism and interpretation -- History.; Wells, H. G. -- (Herbert George), -- 1866-1946 -- Influence.; Wells, H. G. -- (Herbert George), -- 1866-1946; Soviet literature -- English influences.; English literature -- Soviet influences.; Littérature soviétique -- Influence anglaise.; LITERARY CRITICISM -- Comparative Literature.; English literature -- Soviet influences; Influence (Literary, artistic, etc.); Soviet Union; Literary criticism; Criticism, interpretation, etc.; History; Literary criticism.; Critiques littéraires.